Statistics for economics, accounting, and business studies - Barrow, Michael (Harlow, England ; New York : FT Prentice Hall, 2006)
This fourth edition of Statistics for Economics, Accounting and Business Studies is written to provide a clear and concise introduction to a range of statistical concepts and techniques. Throughout the text the author highlights how and why these techniques can be used to solve real-life problems, ensuring that the material is relevant to the experience of the student." "This is a core text for introductory courses in statistics at undergraduate and MBA level. The book will be particularly suitable for economics and accounting students and will also appeal to those taking courses in business studies.
Includes index.
oif 23/07/14 uaj 02/03/2015
Loan
Keywords: Economics - statistics; Commercial statistics; Accounting and business studies - statistics